2023
DOI: 10.1039/d3fo00728f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lacticaseibacillus paracasei strain Shirota supplementation on clinical responses and gut microbiome in Parkinson's disease

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disease characterized by motor issues and a range of nonmotor symptoms. Microbial therapy may be a useful approach for the treatment of PD....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…However, more identified RNA transcripts exhibited a stronger association with the short PFS patient group, namely, 92% (35 out of 38) with a minimum AUC of 7.0. Among them, alkaline, reducing fluidresident Hakubanella thermoalkaliphilus from the Actinomycetota phylum [65] was not yet described in connection with the human microbiome, whereas the genus Lacticaseibacillus, along with other Lactobacillus species described as lactic acid producer probiotics were already heavily implicated in gut health and immunity, including alleviating GI symptoms in Parkinson's disease [66], contribution to cell-wall remodeling and gut microbiome homeostasis [67]. In cancer, the genus has been assigned an anti-proliferative role boosting anti-tumor immunity, but only in colorectal cancer and mouse models [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…However, more identified RNA transcripts exhibited a stronger association with the short PFS patient group, namely, 92% (35 out of 38) with a minimum AUC of 7.0. Among them, alkaline, reducing fluidresident Hakubanella thermoalkaliphilus from the Actinomycetota phylum [65] was not yet described in connection with the human microbiome, whereas the genus Lacticaseibacillus, along with other Lactobacillus species described as lactic acid producer probiotics were already heavily implicated in gut health and immunity, including alleviating GI symptoms in Parkinson's disease [66], contribution to cell-wall remodeling and gut microbiome homeostasis [67]. In cancer, the genus has been assigned an anti-proliferative role boosting anti-tumor immunity, but only in colorectal cancer and mouse models [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are live microorganisms that, when ingested in appropriate amounts, positively affect resident intestinal microbiota and improve the symptomatology of a wide range of chronic diseases, especially GIT ones [48][49][50]. Preliminary human studies have shown improvements in intestinal symptoms [51][52][53], depression [54], and motor and metabolic markers [55]. Murine data support their anti-inflammatory potential in PD therapy [23,56].…”
Section: Non-dietary Gut Microbiota-targeted Interventionsmentioning
confidence: 98%
“…Emerging research posits that pathogenic variants of alpha-synuclein—a hallmark protein in PD—may originate within the gut and ascend to the brain through the vagus nerve, implicating this route in the disease’s early development and progression ( 13 , 22 , 32 , 41 , 46 , 49 , 58–60 ). Additionally, the gut microbiota’s role in neurotransmitter production, such as serotonin and dopamine, which are integral to mood regulation and motor control, respectively, further underscores its potential impact on PD symptomatology ( 13 , 20 , 21 , 25 , 31 , 32 , 35 , 38 , 39 , 42 , 43 , 45 , 48 , 50 , 53 , 61 ).…”
Section: Mechanisms Of Gut Microbiota Influence On Pdmentioning
confidence: 99%
“…In PD, alterations in the production of gut microbiota-derived metabolites may compromise neuronal health and foster neurodegeneration ( 19 , 20 , 22 , 24–26 , 28 , 30–32 , 35–44 , 46–54 , 56–61 ). The microbiota’s capacity to regulate the secretion of gut hormones such as ghrelin and glucagon-like peptide-1 (GLP-1), both noted for their neuroprotective properties, may also be pivotal in modulating PD’s progression ( 23 , 27 , 31 , 33 , 35 , 39 , 53 ).…”
Section: Mechanisms Of Gut Microbiota Influence On Pdmentioning
confidence: 99%
See 1 more Smart Citation